Edaphic microorganisms of Saccharum officinarum; antagonism of Bacillus spp. against Colletotrichum spp. and Endocalyx spp. - Martinez-Netro, Karen Jazmin; Ríos-Aceves, Kevin Eduardo; Rubio-Tinajero, Sarahi; Reyes-Hernández, José; Osorio-Hernández, Eduardo (Ecosistemas y Recursos Agropecuarios, 2025)
Microorganisms that cause diseases in crops are responsible for large economic losses, but there are beneficial microorganisms that act as regulators of pathogens, which generate an antagonistic effect. Therefore, the objective of this research was to isolate and identify fungi and bacteria. of agricultural soil from different sugarcane fields, as well as determining the antifungal activity of Bacillus spp. against the pathogens found. For this, the serial dilution technique was carried out on plates, quantification of colony-forming units (CFU) of both fungi and bacteria, identification at the genus level of phytopathogens and confrontation of Bacillus spp. against them. No significant differences were found between the number of CFU of bacteria or fungi, seven genera of fungi were found: Paecilomyces spp., Chaetomium spp., Fusarium spp., Aspergillus spp., Endocalyx spp., Penicillium spp., and Dictyoarthrinium spp. Regarding the antagonistic effect of Bacillus spp., against phytopathogenic fungi, the strains with the greatest antagonistic effect were B1, B2 and B6. Therefore, it is concluded that Bacillus spp. with the greatest antagonistic effect are B1 from the floor of the wall (S3), B2 and B6 from the open-air dump in Ciudad Victoria, Tamaulipas.